Pharmacotherapeutic options for kidney disease in HIV positive patients. (2nd January 2021) - Tariq, Anam; Kim, Hannah; Abbas, Hashim; Lucas, Gregory M.; Atta, Mohamed G.
ABSTRACT: Introduction: Since the developmentof combined antiretroviral therapy (cART), HIV-associated mortality and the incidence of HIV-associated end-stage kidney disease (ESKD) has decreased. However, in the United States, an increase in non-HIV-associated kidney diseases within the HIV-positive population is expected. Areas Covered: In this review, the authors highlight the risk factors for kidney disease within an HIV-positive population and provide the current recommendations for risk stratification and for the monitoring of its progression to chronic kidney disease (CKD), as well as, treatment. The article is based on literature searches using PubMed, Medline and SCOPUS. Expert opinion: The authors recommend clinicians (1) be aware of early cART initiation to prevent and treat HIV-associated kidney diseases, (2) be aware of cART side effects and discriminate those that may become more nephrotoxic than others and require dose-adjustment in the setting of eGFR ≤ 30ml/min/1.73m 2, (3) follow KDIGO guidelines regarding screening and monitoring for CKD with a multidisciplinary team of health professionals, (4) manage other co-infections and comorbidities, (5) consider changing cART if drug induced toxicity is established with apparent eGFR decline of ≥ 10ml/min/1.73m 2 or rising creatinine (≥0.5mg/dl) during drug–drug interactions, and (6) strongly consider kidney transplant in appropriately selected individuals with end stage kidney failure.